Estimation of the rice yield in the Mekong Delta using dual polarisation TerraSAR-X data - Nguyen, Lam Dao; Phung, Hoang Phi; Juliane, Huth; Phung, Cao Van (VNU Journal of Science: Earth and Environmental Sciences, 2012)
Abstract. Food security has currently become a key global issue due to rapid population growth in many parts ofAsia, as well as the effects of climate change. For this reason, there is a need to develop a spatio-temporal monitoring system that can accurately assess rice area planted and rice production. Changes in rice cultivation systems have been observed in various countries of the world, especially in the Mekong Delta,Vietnam. The changes in cultural practices have impacts on remote sensing methods developed for rice monitoring, in particular, methods using new generation radar data. The objective of the study was to estimate the rice yield using new generation time-series Synthetic Aperture Radar (SAR) imagery. Field data collection and in situ measurement of rice crop parameters were conducted in An Giang province, Mekong Delta in 2010. The average values of the radar backscattering coefficients that corresponded to the sampling fields were extracted from the TerraSAR-X StripMap (TSX SM) images taken during a crop season. The temporal rice backscatter behaviour was analysed for HH (Horizontal transmit and Horizontal receive), VV (Vertical transmit and Vertical receive), and polarisation ratio data. For rice yield estimation, the predictive model based on multiple linear regression analysis [1] between in situ measured yields and polarisation ratios attained good correlation. The high accuracy was found when the rice production estimated from TerraSAR-X data was compared to the government statistics in Autumn Winter 2010 crop at Cho Moi. Thus, it proved to be a potential tool for estimating rice production in the study area. Keywords: Remote sensing, TerraSAR-X, Rice, Mekong Delta.